Pengaruh Motivasi Kerja dan Displin Kerja terhadap Kinerja Karyawan pada PT Pegadaian Cabang Syariah Pondok Aren Tangerang Selatan - Destyaningsih Sutrisno; Bilgah Bilgah (Ebisnis Manajemen, 2025)
PT Pegadaian (Persero) CPS Pondok Aren Tangerang Selatan. Location address: Jl. Ceger Raya No. 99 Bloom Residence Ruko I, Tangerang Selatan, Banten. The office of PT. Pegadaian CPS Pondok Aren branch in Tangerang Selatan, Banten serves Rahn Business, Sharia Pawn, Arrum, Amanah, Mulia, EmasKu, Gold Savings, Gold Savings, MPO (Purchase and Payment of Telephone Bills, Electricity, Water, Tickets, Internet, Pay TV, BPJS Contribution Payments, etc.). This study aims to analyze work motivation, work discipline and employee performance at PT Pegadaian Sharia Branch Pondok Aren Tangerang Selatan. This research method is a quantitative method. The population in this study were employees of PT Pegadaian Sharia Branch Pondok Aren Tangerang Selatan. The sample in this study amounted to 40 respondents. The data collection instrument used a questionnaire. The independent variables are work motivation and work discipline while the dependent variable is employee performance. The data analysis method used is multiple linear regression. The results of this study indicate that work motivation and work discipline have a simultaneous and significant effect on employee performance as indicated by the significant level F <α (0.000 <0.05) and the determination of R Square on the influence of motivation (X1) and work discipline (X2) on employee performance (Y) obtained a value of 0.900 or 90%. This means 90%. Partially, work motivation has a significant effect on employee performance of 0.005, work discipline has a significant effect on employee performance of 0.000.